Customer Segmentation Using K-Means Clustering for Personalized Marketing Campaigns - Purushottam Perapu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In today’s hyper-competitive digital marketplace, understanding customer behavior is paramount for developing effective marketing strategies. As busi- nesses increasingly accumulate large volumes of customer data, advanced data mining techniques have become essential for extracting meaningful in- sights. One such approach is customer segmentation, which divides a cus- tomer base into distinct groups with shared characteristics or behaviors. This research focuses on implementing the K-Means clustering algorithm—a pop- ular unsupervised machine learning technique—to achieve customer segmen- tation for designing personalized marketing campaigns. The primary objective of this study is to analyze customer purchase be- havior and demographic attributes using the K-Means clustering method and evaluate its effectiveness in identifying actionable customer segments. We employ a real-world retail dataset containing variables such as age, in- come, frequency of purchase, total expenditure, and recency. Preprocessing steps such as normalization, feature selection, and dimensionality reduction are applied to improve clustering accuracy. The optimal number of clusters is determined using techniques like the Elbow Method and Silhouette Analysis to ensure meaningful groupings. The clustering results reveal distinct customer segments based on pur- chasing patterns and behavioral trends. For example, one cluster may consist of high-value, loyal customers, while another might include infrequent, price- sensitive buyers. These insights enable businesses to tailor marketing cam- paigns more precisely—offering premium services to high-value customers and promotions or discounts to price-conscious groups. The study also em- phasizes the importance of visual analytics tools such as scatter plots and heatmaps in interpreting clustering outcomes for strategic decision-making. This research demonstrates that K-Means clustering provides a scalable and interpretable solution for customer segmentation, capable of uncover- ing hidden patterns that traditional demographic-based segmentation might overlook. Furthermore, it showcases how machine learning can empower mar- keters to transition from generic mass marketing to data-driven personalized engagement, thereby improving customer satisfaction and marketing ROI. The findings of this research can be integrated into Customer Relationship Management (CRM) systems to enhance customer retention strategies and lifetime value prediction. Limitations such as sensitivity to the initial cen- troids and fixed cluster count are acknowledged, with suggestions for future work including advanced clustering techniques like DBSCAN and hierarchical clustering, as well as the integration of behavioral and psychographic data.
Keywords: Customer segmentation; K-Means clustering; machine learning; unsuper- vised learning; personalized marketing; customer behavior analysis; data- driven marketing; retail analytics; CRM systems; purchasing patterns; mar- keting ROI; customer profiling; feature engineering; clustering accuracy; mar- keting strategy optimization; consumer behavior; data preprocessing; cluster visualization; marketing intelligence; customer lifetime value